2018
DOI: 10.1002/hed.25352
|View full text |Cite
|
Sign up to set email alerts
|

Early (90‐day) mortality after radical radiotherapy for head and neck squamous cell carcinoma: A population‐based analysis

Abstract: Background A retrospective, population‐based analysis of 90‐day mortality in patients with squamous cell carcinoma of the head and neck treated with radiotherapy was performed to determine the early mortality rate and associated risk factors. Methods Data were abstracted for all consecutive patients with cancer of the head and neck treated from 1998 to 2014 at the BC Cancer Agency with curative intent radiotherapy (n = 5658). Logistic regression analysis was used to determine factors associated with early mort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 32 publications
4
24
3
Order By: Relevance
“…Indeed, previous studies have suggested that age, pneumonia, sepsis, hemiplegia, moderate or severe renal disease, presence of other cancers, and non-HNSCC metastatic cancers are independent poor prognostic factors of overall mortality risk in patients with HNSCC receiving curative treatments. 5,6,24,[34][35][36][37][38] The major causes of 90-day mortality in patients with HNSCC were aspiration pneumonia, infections, and sepsis. [39][40][41][42][43] The mechanisms of aspiration pneumonia, infections, and sepsis were most likely from chemotherapy-related immunocompromised sepsis, RT-related poor swallowing-induced aspiration pneumonia, and comorbidity-related poor self-care ability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, previous studies have suggested that age, pneumonia, sepsis, hemiplegia, moderate or severe renal disease, presence of other cancers, and non-HNSCC metastatic cancers are independent poor prognostic factors of overall mortality risk in patients with HNSCC receiving curative treatments. 5,6,24,[34][35][36][37][38] The major causes of 90-day mortality in patients with HNSCC were aspiration pneumonia, infections, and sepsis. [39][40][41][42][43] The mechanisms of aspiration pneumonia, infections, and sepsis were most likely from chemotherapy-related immunocompromised sepsis, RT-related poor swallowing-induced aspiration pneumonia, and comorbidity-related poor self-care ability.…”
Section: Discussionmentioning
confidence: 99%
“…The 90-day mortality rate after completion of RT is a proposed measure for improving cancer outcomes and reducing avoidable treatment-related toxic effects. [5][6][7] In the United Kingdom, the 90-day mortality rate among patients with HNSCC after completion of RT (3.6% per the Data Audit for Head and Neck Oncology 8 ) has been proposed as the reference to indicate treatment suitability, reduce treatment-related mortality, and improve cancer outcomes. 7 Similarly, the Scottish Cancer Taskforce recommended that the 90-day mortality of patients with HNSCC after treatment be considered a guideline for ensuring the quality of care and appropriate curative treatment administration.…”
Section: Introductionmentioning
confidence: 99%
“…Our results might be influenced by the publicly funded, well‐coordinated provincial cancer care program in BC 3 . These results may not be generalizable for other jurisdictions with smaller rural centers, which might not be as well connected with a specialized tertiary center as is the case in the Canadian health care context.…”
Section: Discussionmentioning
confidence: 74%
“…In a previous population‐based study performed in British Columbia (BC), Canada, we found a 90‐day mortality in HNC patients with squamous cell carcinoma (SCC) of 3.6% 3 . More than half of patients in small and rural areas live more than 2 h driving distance from cancer centers in BC 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Clinically advanced cases make up about 50%, despite the rapid development of medical technology, as well as the increasingly improved early diagnosis technique of HNSCC (2)(3)(4). Over the past 20 years, great achievements have been made in the surgical method (5), radiotherapy (6), and chemotherapy (7); however, the 5-years survival rate for HNSCC, especially for the advanced patients, has not yet been remarkably improved (8). This ineffectiveness of current therapies underscores the urgent need for new discoveries leading to more effective treatment pathways.…”
Section: Introductionmentioning
confidence: 99%